Effects of form of sulfa on medicated water consumption - Schoneweis, D.; Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Four-week old weaned pigs demonstrated a marked preference in medicated water consumption depending on form of sulfa. Medicated water consumption was greatly reduced when sulfamethazine was used. Sulfadimethoxine was the most readily accepted one evaluated and sulfathazine preferred least.
Keywords: Swine; Sulfa; Medicated water consumption